Initial discovery of microplastic pollution in Mnemiopsis leidyi (Ctenophora: Lobata) - Yapuchura Ocaris, Enrique Ronald (2023)
The production of plastics has exponentially increased over time such that the observation of microplastics in the oceans has become a major concern given how frequently these particles and marine biota may interact. Microplastics can be ingested by diverse species, including invertebrates, which can lead to physical damage due to their small size and potentially chemical damage related to the ingestion of monomers, polymeric additives, or adsorbed chemicals. This study reports on the first evidence of microplastics in Mnemiopsis leidyi. Microplastics were described by type, quantified, and had their chemical composition identified. In total, 328 samples of microplastic (MP) candidates were observed: blue fibers were the most abundant, followed by black, red, and green fibers as well as blue fragments. Three types of microplastics were chemically identified as polyurethane, unplasticized polyvinylchloride, and polyethylene polylauryllactam. Overall, this study demonstrated that Mnemiopsis leidyi have the capacity to incorporate microplastics. Although more studies are needed, Mnemiopsis leidyi is relatively abundant on the Atlantic coast and should be recommended for use as a bioindicator for microplastics.